Effects of the Vertical Malocclusion Types on the Dimension of the Mandibular Condyle - Merve Göymen; Ayşegül Güleç (Galenos Yayinevi, 2017)
Objective:This study aimed to find the relationship between mandibular condyle morphology and dental malocclusion in patients with anterior open bite, deep bite, and normal overbite.Methods:Eighty patients were included in this retrospective study. All patients had skeletal Class II pattern. The initial panoramic radiographs of patients were digitized using a software program, and groups were compared in terms of condylar height, width, area, and perimeter. In addition, changes in the condyle surface shape were detected using the same panoramic radiographs.Results:The mean width was 1.55±0.06 cm in the open bite group, 1.48±0.06 cm in the deep bite group, and 1.38±0.07 cm in the normal bite group. The mean height was 2.17±0.08 cm in the open bite group, 1.95±0.06 cm in the deep bite group, and 1.97±0.08 cm in the normal bite group. The mean area was 2.33±0.13 cm2 in the open bite group, 2.09±0.11 cm2 in the deep bite group, and 2.04±0.14 cm2 in the normal bite group. There was no statistical significant difference between groups in terms of condyle measurements and condyle surface shapes.Conclusion:The results suggest that the vertical malocclusion type does not have a considerable effect on the mandibular condyle measurements and surface shapes.